Women, Gender Norms, and Natural Disasters in Bangladesh. - Juran, Luke; Trivedi, Jennifer (Geographical Review, 2015)
The article explores the impact of natural disasters on women in Bangladesh. Emphasis is given to topics such as the role of gender and social variables in gaps in mortality, the relationship between gender inequality and risk, and gender-based segregation practices that restrict female mobility in disasters.